METHOD OF ADAPTIVE PROCESS MANAGEMENT USING CASE BASED REASONING - Чалий, С. C.; Левикін, І. В. (Science-based technologies, 2016)
Case-based approach aims to use existing experience in dealing with new challenges. Case includes experience in a structured performance objectives as well as a description of its process solutions. In implementing the approach of case precedent adaptation procedure is performed prior to the relevant management process. In process management it is not possible to adapt business processes and change the sequence of their works at run time, which is especially important when you access shared resources. This shows the relevance of the problem of adaptive business process management. A method for adaptive process management using case – based reasoning is proposed. The method comprises the following steps: adaptation of precedent process models; execution of processes according to a predetermined pattern in a sequence of actions; adding a new process to the set of executable given the delays in access to shared resources. The proposed method, in contrast to the existing implements the management of multiple business processes that use shared resources. The method makes it possible to assess the feasibility of time constraints.